FENOMENA FANWAR DAN FANATISME ANTAR FANDOM K-POP DI MEDIA SOSIAL TWITTER - Pohan, Syafruddin; Gustiana, Zelfi Nanda (CV. Kalimasada Group, 2023)
The development of technology has triggered the rapid entry of culture from various regions including abroad, one of which is the entry of K-Pop music which is much loved by the public, including in Indonesia. The popularity of K-pop has created groups that idolize K-pop idols. The large number of K-pop groups makes the competition between idols in which their fandoms participate, creating fanwars based on fanwar behavior. This study aims to analyze the behavior of fanwar and fanaticism which is carried out through the social media Twitter. This study used a descriptive qualitative method supported by a literature review. The result of this research is that fanwar behavior is triggered by fanaticism and it is easy to do fanwar through social media because of the existence of a base account.